APLIKASI PEMERIKSAAN PERSYARATAN YUDISIUM PADA PROGRAM STUDI TEKNIK INFORMATIKA UNIVERSITAS KRISTEN PETRA - Santoso, Leo Willyanto; ., Yulia; Julita, Luwuk Melly (Jurnal Informatika, 2012)
Informatics Engineering Department Petra Christian University do inspection process for judicium manually. This manual process spends considerable time and difficulty in adjusting to the curriculum and regulations. Based on the problems faced by the Department of Informatics, the author develops an application to help speed up and simplify the judicium inspection. This application includes the setting of curriculum, setting fields of study, inspection requirements judicium, determining areas of study graduated students and graduation report. This application was created using ASP.Net programming language and MYSQL as a database. Based on the testing processes, this application has been able to meet the needs of Department of Informatics in the judicium inspection process.